Microbial cellulose dressing compared with silver sulphadiazine for the treatment of partial thickness burns: A prospective, randomised, clinical trial. Issue 8 (December 2018) - Aboelnaga, Ahmed; Elmasry, Moustafa; Adly, Osama A.; Elbadawy, Mohamed A.; Abbas, Ashraf H.; Abdelrahman, Islam; Salah, Omar; Steinvall, Ingrid
Highlights: We investigated two wound dressings for treatment of superficial burns. We compared microbial cellulose with silver sulphadiazine cream. A prospective randomised clinical trial design. Microbial cellulose dressing was a better treatment of partial thickness burns. Fewer dressings were done associated with low pain scores. Abstract: Background: The current treatment for partial thickness burns at the trial site is silver sulphadiazine, as it minimises bacterial colonisation of wounds. Its deleterious effect on wound healing, together with the need for repeated, often painful, procedures, has brought about the search for a better treatment. Microbial cellulose has shown promising results that avoid these disadvantages. The aim of this study was therefore to compare microbial cellulose with silver sulphadiazine as a dressing for partial thickness burns. Method: All patients who presented with partial thickness (superficial and deep dermal) burns from October 2014 to October 2016 were screened for this randomised clinical trial. Twenty patients were included in each group: the cellulose group was treated with microbial cellulose sheets and the control group with silver sulphadiazine cream 10 mg/g. The wound was evaluated every third day. Pain was assessed using the Face, Legs, Activity, Cry, Consolability (FLACC) scale during and after each procedure. Other variables recorded were age, sex, percentage total body surface area burned (TBSA%), clinical signs of infection, time for epithelialisation and hospital stay. Linear multivariable regression was used to analyse the significance of differences between the treatment groups by adjusting for the size and depth of the burn, and the patient's age. Results: Median TBSA% was 9% (IQR 5.5–12.5). The median number of dressing changes was 1 (IQR 1–2) in the cellulose group, which was lower than that in the control group (median 9.5, IQR 6–16) (p < 0.001). Multivariable regression analysis showed that the group treated with microbial cellulose spent 6.3 (95% CI 0.2–12.5) fewer days in hospital (p = 0.04), had a mean score that was 3.4 (95% CI 2.5–4.3) points lower during wound care (p < 0.001), and 2.2 (95% CI 1.6–2.7) afterwards (p < 0.001). Epithelialisation was quicker, but not significantly so. Conclusion: These results suggest that the microbial cellulose dressing is a better first choice for treatment of partial thickness burns than silver sulphadiazine cream. Fewer dressings of the wound were done and, combined with the low pain scores, this is good for both the patients and the health care system. The differences in randomisation of the area of burns is, however, a concern that needs to be included in the interpretation of the results.